Hubungan Pola Konsumsi Makanan Cepat Saji dengan Keteraturan Siklus Menstruasi pada Remaja Putri Kelas XI di SMAN 7 Mataram - Hadi Suryatno; I Gusti Ayu Mirah Adhi; Stevani Octavia Ratu; Febriati Astuti; Nurul Ilmi; Endah Sulistiyani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Background: Menstruation is the periodic release of blood and tissue mucosa from the inner lining of the uterus which comes out through the vagina. According to WHO, in 2020 the prevalence of menstrual cycle disorders in women was around 45%. The prevalence of menstrual disorders in the world such as 74.5% in Malaysia, 90% in America, and 54.89% in Indonesia. One of the factors causing menstrual cycle disorders is frequent consumption of fast food such as sweets, pickles, and fried foods. Purpose : The aim of this research is to find out whether there is a correlation between fast food consumption patterns and the regularity of the menstrual cycle in class XI female students at SMAN 7 Mataram. Method: It is a quantitative research with a cross-sectional method. The sample was 107 students was obtained using inclusion and exclusion purposive sampling techniques. The instruments used were dietary pattern questionnaires and menstrual questionnaires. Data analysis used chi- square. Results: Based on the research results, 65 respondents (60.7%) were categorized as having an unhealthy eating pattern, and 42 respondents (79.3%) were categorized as having a healthy eating pattern. As many as 67 respondents (62.6%) experienced irregular menstrual cycles, and as many as 40 respondents (374) experienced regular menstrual cycles. The Chi-Square test results showed that the value is 0.002, which means <0.005. Conclusion: There is a correlation between fast food consumption patterns and menstrual cycle regularity